Middle- and long-term results after iris-fixated phakic intraocular lens implantation in myopic and hyperopic patients: a meta-analysis. Issue 1 (January 2020) - van Rijn, Gwyneth A.; Gaurisankar, Zoraida S.; Ilgenfritz, Antonio P.; Lima, José Eduardo E.; Haasnoot, Geert W.; Beenakker, Jan-Willem M.; Cheng, Yanny Y. Y.; Luyten, Gregorius P. M.
Abstract : The iris-fixated phakic intraocular lens (pIOL) has been available for over 25 years. To provide a clear picture of outcomes and risks, for this systematic review and meta-analysis, the literature was searched for reports on middle- and long-term effects. The iris-fixated phakic intraocular lens (pIOL) has been available for over 25 years. To provide a clear picture of outcomes and risks, for this systematic review and meta-analysis, the literature was searched for reports on middle- and long-term effects of iris-fixated pIOLs on myopic and hyperopic eyes with a follow-up of at least 2 to 4 years. Visual and refractive results after implantation for correction of myopia are positive and the complication rate is low. Endothelial cell loss appears to be at an acceptable rate, although the range of endothelial cell change is too wide to draw firm conclusions. Care should be taken when considering an iris-fixated pIOL for hyperopic eyes because complication rates, particularly pigment dispersion, might be higher than those in myopic eyes. More well-designed, long-term studies are needed, especially in hyperopic eyes. The authors advocate for standardized reporting of refractive surgery data. Initiatives proposed by journal authors and editors to achieve uniformity should be supported. Abstract : Refractive and visual results are positive after implantation of an iris-fixated pIOL. Overall complication rates are low, although care should be taken when considering an iris-fixated pIOL in hyperopic eyes.